2012
DOI: 10.1186/1475-2891-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a single oral dose of vitamin D3 (70,000 IU) in pregnant and non-pregnant women

Abstract: BackgroundImprovements in antenatal vitamin D status may have maternal-infant health benefits. To inform the design of prenatal vitamin D3 trials, we conducted a pharmacokinetic study of single-dose vitamin D3 supplementation in women of reproductive age.MethodsA single oral vitamin D3 dose (70,000 IU) was administered to 34 non-pregnant and 27 pregnant women (27 to 30 weeks gestation) enrolled in Dhaka, Bangladesh (23°N). The primary pharmacokinetic outcome measure was the change in serum 25-hydroxyvitamin D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…The response to the higher-dose supplement regimen was also assessed in a cohort of non-pregnant participants that served as a separate comparison group. The present study builds on previously reported observations of single-dose vitamin D3 pharmacokinetics in the same setting [13]. …”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The response to the higher-dose supplement regimen was also assessed in a cohort of non-pregnant participants that served as a separate comparison group. The present study builds on previously reported observations of single-dose vitamin D3 pharmacokinetics in the same setting [13]. …”
Section: Introductionmentioning
confidence: 58%
“…NH was studied before enrolment of PH, to establish safety of the high-dose regimen in non-pregnant women prior to its use in pregnant women. As an additional safety measure, the response to a single initial dose vitamin D3 (70,000 IU) was observed in a separate cohort, prior to the initiation of enrollment of cohorts of participants who received weekly doses [13]. A preceding report of single-dose vitamin D3 pharmacokinetics included data from participants in weekly-dose groups PH and NH, but only from days 0 to 7 ( i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma folate concentrations showed no statistically significant changes [221,222], but conflicting change directions were seen in the mean values, depending on the dose [222]. Similarly, vitamin D3 showed conflicting change directions in exposure parameters, which were statistically non-significant [223,224]. …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, we did not document any notable pregnancy-related hypersensitivity to a vitamin D dose of 70,000 IU in terms of its effects on calcium homeostasis. However, the unpredictability of the 25(OH)D response at the individual level, previous reports of adverse effects of large single doses [23], and the theoretical disadvantages of excessive fluctuations in vitamin D status [29] suggest that the use of large single or infrequent intermittent doses of vitamin D3 may be physiologically disadvantageous despite its practical appeal. Therefore, these data principally support the further investigation of single doses equal to or less than 70,000 IU in the context of intermittent (e.g., weekly or biweekly) antenatal dosing regimens.…”
Section: Discussionmentioning
confidence: 95%